MENENGOK KEMBALI POTRET GERAKAN DAKWAH DARUL ARQAM - Muridan, Muridan (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2007)
Darul Arqom was a movement established in 1968 by a Malaysian politician. Its background was the desire to actualize Islam comprehensively like the one in the age of the Prophet. The followers of this movement tried to perform more dzikir and to imitate the way of eating and clothing in the prophet era. In aqidah, Darul Arqom held tightly the principals of Ahlussunnah Waljamaah. In this case, Darul Arqom interpreted the nature of Ahlussunnah Waljamaah as a pure Islamic teaching as it had been applied by the Prophet and his followers. In Fiqh, it refered to Imam Syafi’i and in mysticism, it refered to Imam Ghazali.